Preferential action of eptazocine, a novel analgesic, with opioid receptors in isolated guinea pig ileum and mouse vas deferens preparations - Tamura, T; Ogawa, J; Taniguchi, T; Waki, I (Nihon yakurigaku zasshi, 1990)
Actions of eptazocine, a novel analgesic, on isolated smooth muscle preparations were investigated. Eptazocine (10(-5) M) slightly inhibited electrically-driven twitch-tension in guinea pig ileum preparations sensitive to mu- and kappa-agonists, and this effect was antagonized by 10(-7) M naloxone. Eptazocine (10(-5)-10(-4) M) inhibited such an effect by the mu-agonist morphine. In mouse vas deferens preparations having delta-, mu- and kappa-receptors, eptazocine (10(-7) M-) inhibited the twitch-tension in a dose-dependent manner, being hardly inhibited by naloxone. On the other hand, MR-2266 (10(-6) M), a relatively selective kappa-receptor antagonist, inhibited the eptazocine effect. The Ke (equilibrium dissociation constant) value of naloxone against eptazocine was 325 nM and the Ke value of MR-2266 against eptazocine was 33.2 nM, showing that MR-2266 was 9.79-fold more effective than naloxone. These results suggest that eptazocine acted as a mu-receptor antagonist and as a kappa-receptor preferential agonist in isolated smooth muscle preparations.